Climate-smart decision support system for assessing water demand patterns under future climate change for Kerian rice irrigation scheme, Malaysia - Mohd Nasir, Muhammad Adib (2019)
The uncertainty of water availability for irrigation supply affects the sustainable rice production under the likely evolving climate change impacts. In recent decades, the growth of populations and drastically economic development in urban areas have resulted in a severe water shortage in many countries with 70% of total global water used for the agricultural sector. Climatic changes cause an increase in temperature, changes in rainfall patterns and other hydrogeological variables. These changes will have adverse effects on hydrological systems and water resources management, which are important sources for agriculture. Therefore, analyzing the impacts of climate change on water demand and management of water resources systems to assess agricultural production, especially for rice, has become an important issue.